2009
DOI: 10.1080/10683160802190871
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive skills programmes for offenders

Abstract: Following the impact of the meta-analyses and 'What Works' in offender treatment, cognitive skills programmes for offenders have become widely used in both the community and in custody. This overview is primarily concerned with the issue of effectiveness: do cognitive skills programmes have an effect on reoffending? The extant evidence suggests that there are lower rates of reoffending among offenders who complete cognitive skills programmes. However, there is a debate in the literature as to whether this 'com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 70 publications
2
26
0
3
Order By: Relevance
“…Uit verschillende meta-analyses blijkt dat met name cognitieve gedragsprogramma's effectief zijn in het verminderen van recidive in vergelijking met gebruikelijke zorg of gedragsprogramma's (Hollin & Palmer, 2009;Landenberger & Lipsey, 2005;Pearson, Lipton, Cleland, & Yee, 2002). In deze effectiviteitsstudies is echter vaak weinig bekend over de manier waarop de interventie in de praktijk wordt uitgevoerd, oftewel de programma-integriteit van een interventie (Durlak & DuPre, 2008;Landenberger & Lipsey, 2005).…”
Section: Inleidingunclassified
“…Uit verschillende meta-analyses blijkt dat met name cognitieve gedragsprogramma's effectief zijn in het verminderen van recidive in vergelijking met gebruikelijke zorg of gedragsprogramma's (Hollin & Palmer, 2009;Landenberger & Lipsey, 2005;Pearson, Lipton, Cleland, & Yee, 2002). In deze effectiviteitsstudies is echter vaak weinig bekend over de manier waarop de interventie in de praktijk wordt uitgevoerd, oftewel de programma-integriteit van een interventie (Durlak & DuPre, 2008;Landenberger & Lipsey, 2005).…”
Section: Inleidingunclassified
“…Whilst quantitative evaluations and meta analyses of New Zealand-based criminogenic rehabilitation programmes and international offence-related treatment interventions are in abundance Hollin & Palmer, 2009;McGuire, 2002;Polaschek et al 2005;Smith, Goggin &Gendreau, 2001 andTong &Farrington, 2006) the same cannot be said for qualitative methodologies. Chwalisz, Shah and Hand (2008) observed that "Qualitative research methods have much to contribute to theoretical and applied knowledge in rehabilitation psychology.…”
Section: The Evolution Of Rehabilitative Treatmentmentioning
confidence: 99%
“…The consistent message amongst researchers (Andrews & Bonta, 1998, Hollin & Palmer, 2009, McMurran & Theodosi, 2007and Tong & Farrington, 2006 is that failure to complete rehabilitative programmes is detrimental to the long-term wellbeing of the former participants, as it correlates with re-offending. McMurran and McCulloch (2007) contend that, in addition to the adverse interpersonal effects of non-completion for the individual participant, noncompletion holds particular relevance on a macro-level.…”
Section: Completion and Dropout/reconvictionmentioning
confidence: 99%
See 2 more Smart Citations